2007
DOI: 10.1167/iovs.07-0483
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Evaluation of Retinal Ganglion Cell Function and IOP in the DBA/2J Mouse Model of Glaucoma

Abstract: Results indicate that inner retina function in DBA/2J mice progressively decreases after 3 months of age, and it is nearly abolished by 10 to 11 months, whereas outer retina function shows little change and the RNFL thickness is relatively spared. This result suggests that surviving RGCs may not be functional. Progression of inner retinal dysfunction is strongly associated with increased IOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
115
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(146 citation statements)
references
References 77 publications
23
115
1
1
Order By: Relevance
“…This is consistent with findings of a considerable number of surviving axons in older optic nerves, even with diminished physiological activity (Fig. 6B) (14,17,36).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with findings of a considerable number of surviving axons in older optic nerves, even with diminished physiological activity (Fig. 6B) (14,17,36).…”
Section: Discussionsupporting
confidence: 92%
“…A small number of younger DBA/2 (3-5 mo) had transport deficits without IOP elevation (Fig. 2), so additional pathogenic mechanisms must be at work early (30,36). Retrograde transport from the SC to the retina in the DBA/2 is maintained at 20% to 30% capacity up to 18 mo of age (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous results, reporting IOP increase from an age of 6 months [19,31], we showed that IOP is already elevated in 7 month DBA/2J mice remaining elevated at later ages. We previously demonstrated that IOP elevation plays a critical role in influencing visual response and in causing RGC dysfunction [19].…”
Section: Discussionsupporting
confidence: 93%
“…IOP was already elevated in 7 month-old-DBA/2J mice [31] (C57BL/6J control mice, n=20 eyes, mean=8.12 mmHg, SEM=0.34; 3 month DBA/2J, n eyes=20, mean=8.10 mmHg, SEM=0.33; 7 month DBA/2J, n eyes=12, mean=11.59 mmHg, SEM=0.40; 10-13 month DBA/2J, n eyes=12, mean=13.00 mmHg, SEM=0.65; 15-18 month DBA/2J, n eyes =12, mean=12.85 mmHg, SEM=0.62) shown in figure 1A. These data are in agreement to previous results [19]; here we show that IOP elevation in DBA/2J mice persists at the late ages of 13-18 months.…”
Section: Resultsmentioning
confidence: 90%
“…These mice develop glaucoma as a result of iris pigment dispersion and atrophy of the iris stroma caused by mutations in Glycoprotein non-metastatic b and Tyrosinase-related protein 1 (John et al, 1998). Pigment accumulation in the trabecular meshwork causes clogging and reduced flow of aqueous humor, causing a moderate increase in IOP between 2 and 6 months and a strong increase between 8 and 12 months (Saleh et al, 2007;Harazny et al, 2009). The increase in IOP produces changes in the retina and optic nerve (Libby et al, 2005;Pérez de Lara et al, 2014) Most of the experiments performed to date with melatonin and 5-MCA-NAT have been carried out in either normotensive animals (Pintor et al, 2001) or in hypertensive/glaucoma conditions (Serle et al, 2004;Martínez-Águila et al, 2013), but not in an animal model that develops the disease spontaneously.…”
Section: Introductionmentioning
confidence: 99%